(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This study intends to analyze the influence of principal leadership and work motivation on teacher performance at As-Shofa Foundation in Pekanbaru. The background of the study is rooted in the importance of teacher performance as a determinant of educational quality, as well as the strategic role of principals and work motivation in improving teacher work quality. Quantitative approach, was used in the study, with a sample of 104 teachers chosen by simple random sampling technique. Data were analyzed using descriptive statistics, simple linear regression, and multiple linear regression. Results revealed that principal leadership had a significant effect on teacher performance with a contribution of 71.5%. Meanwhile, work motivation did not have a significant effect on teacher performance, indicating that teachers are still able to carry out their professional tasks without strong external encouragement. Simultaneously, principal leadership and work motivation had a significant effect on teacher performance with a combined contribution of 71.5%. This finding confirms that the role of the principal as an educational leader is crucial in determining the quality of teacher performance, while work motivation should be raised through policies and a more supportive work environment. This study brings a contribution towards the development of educational management science, particularly determinants of teacher performance. Work motivation holds no significant influence on teachers performance at the As-Shofa Foundation in Pekanbaru. The strong managerial role of the foundation and the teachers’ sense of responsibility for their duties are the reasons why work motivation does not influence performance. However, this study is limited to only one foundation.